Forecasting euro area inflation using dynamic factor measures of underlying inflation - Gonzalo Camba-Méndez; George Kapetanios (European Central Bank (ECB), 2004)
Standard measures of prices are often contaminated by transitory shocks. This has prompted economists to suggest the use of measures of underlying in?ation to formulate monetary policy and assist in forecasting observed in?ation. Recent work has concentrated on modelling large datasets using factor models. In this paper we estimate factors from datasets of disaggregated price indices for European countries. We then assess the forecasting ability of these factor estimates against other measures of underlying in?ation built from more traditional methods. The power to forecast headline in?ation over horizons of 12 to 18 months is adopted as a valid criterion to assess forecasting. Empirical results for the ?ve largest euro area countries as well as for the euro area are presented.
Keywords: E31; C13; C32; 330; Core Inflation; Dynamic Factor Models; forecasting